2019
DOI: 10.1016/j.mex.2019.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Development of a control task for clarifying the neural mechanisms underlying tool-use behavior in rats (Rattus norvegicus)

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Testing the nocturnal rodents during the dark phase would be needed to detect their cognitive abilities more appropriately in future studies ( Balcombe, 2010 ). Moreover, only male rats were used as the subjects in the present studies, as were the previous rat studies ( Nagano and Aoyama, 2017a , b ; Nagano, 2019a , b , 2021 ). To testify about the generality of the relationship between the motion control and tool-manipulation, testing with female rats would be needed in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Testing the nocturnal rodents during the dark phase would be needed to detect their cognitive abilities more appropriately in future studies ( Balcombe, 2010 ). Moreover, only male rats were used as the subjects in the present studies, as were the previous rat studies ( Nagano and Aoyama, 2017a , b ; Nagano, 2019a , b , 2021 ). To testify about the generality of the relationship between the motion control and tool-manipulation, testing with female rats would be needed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have investigated tool-use behavior in relatively low-visual-acuity rodents ( Prusky et al, 2002 ), including rats ( Rattus norvegicus ) ( Nagano and Aoyama, 2017a , b ; Nagano, 2019a , b , 2021 ) and degus ( Octodon degus ) ( Okanoya et al, 2008 ; Kumazawa-Manita et al, 2013 ) in controlled experimental settings. Previous studies on rats have reported that these rodents manipulated a rake-shaped tool based on the position of the food reward placed beyond their reach after undergoing tool-use training ( Nagano and Aoyama, 2017b ; Nagano, 2019b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation